The influence of solar power and solar flux on the efficiency of polycrystalline photovoltaics installed close to a river - Armstrong O. Njok; Ferdinand A. Kamgba; Manoj Kumar Panjwani; Fareed H Mangi (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
There is an increasing focus on utilizing the renewable energy resources, especially solar energy as the fossils are expected to deplete in near future. Solar Photovoltaics have remained of particular interest because of their relative lower overall efficiencies .Most researchers are trying to enhance the overall performance of Solar Photovoltaic and trying to study factor that may possible lead to an increase in the overall performance of a Solar Photovoltaic Panels. A thorough investigation was carried out to study the influence of solar power and solar flux on the performance parameters of Photovoltaic (Polycrystalline). The data used in the research was obtained by in-situ measurement approach using an SM206 precision digital solar power meter, a digital solar flux meter, and an M890C+ digital Multimeter. The result obtained shows an interesting correlation for current, efficiency and solar power as well as for solar flux which indicates that high solar power and solar flux positively enhances the performance of the photovoltaic. The results also reveal that once the solar power or solar flux reaching the photovoltaic exceeds 200W/m2 or 20Klux, the voltage from the photovoltaic approaches maximum and remains fairly stable irrespective of the amount of solar power or solar flux reaching the photovoltaic. The data collected for three months, July, August and September shows prediction efficiency of 87 %, 63% and 71% at 11:30am, 12:30 pm and 10:30 am respectively.